2009
DOI: 10.1111/j.1365-2621.2008.01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and functional properties of full fat and defatted cashew kernel flours

Abstract: Full fat and defatted cashew kernel flours were prepared and analysed for their physicochemical and functional properties. There were significant increase in protein and carbohydrate contents of the flour as a result of defatting. The defatted flour possessed higher Ca, P, Na and K contents. It had improved gel strength, foaming and emulsion properties. Foam capacity for the full fat and defatted flours increased from 42% to 50% and 55% to 57% with increased NaCl concentration up to 0.25 and 0.05 m, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 14 publications
(17 reference statements)
5
22
0
Order By: Relevance
“…Ash (4.61 g/100 g) and crude fiber (0.51 g/100 g) contents in the DESM were also higher than in the WESM (ash=3.63; crude fiber=0.34 g/ 100 g). This effect of defatting on the different chemical parameters coincides with that reported in other studies (Alobo et al 2009;Rodríguez-Miranda et al 2012). Energy content in the DESM (1,755.71 kJ/100 g DM) was lower than for the WESM (2,232.55 kJ/100 g d.b.…”
Section: Proximate Compositionsupporting
confidence: 90%
See 3 more Smart Citations
“…Ash (4.61 g/100 g) and crude fiber (0.51 g/100 g) contents in the DESM were also higher than in the WESM (ash=3.63; crude fiber=0.34 g/ 100 g). This effect of defatting on the different chemical parameters coincides with that reported in other studies (Alobo et al 2009;Rodríguez-Miranda et al 2012). Energy content in the DESM (1,755.71 kJ/100 g DM) was lower than for the WESM (2,232.55 kJ/100 g d.b.…”
Section: Proximate Compositionsupporting
confidence: 90%
“…In the DESM, protein content was higher than in other defatted seed byproducts such as neem Azadiracha indica (24.10 g/100 g) (Romero and Vargas 2005), rapeseed Brassica olerácea L. (32.85 g/100 g) (Gonçalvess et al 1997) and chickpea (23.53 g/100 g) (Ionescu et al 2009), but lower than those of peanut Arachis hypogaea L. (46.6 g/ 100 g) (Ferreyra et al 2007), cashew Anacadium occidentale (46.50 g/100 g) (Alobo et al 2009) and pumpkin seed (64.13 g/100 g) (Rodríguez-Miranda et al 2012). According to Bressani (2002), higher level of protein content of seed materials has nutritional significanse, since moderate intake of these sedes will greatly increase the total dietary protein intake of the consumers.…”
Section: Proximate Compositionmentioning
confidence: 95%
See 2 more Smart Citations
“…As result of defatting, the protein content of the flour increased significantly (P < 0.05) from 36.18 to 62.76 g ⁄ 100 g. The defatted flour exhibited increases in carbohydrate and ash contents. Earlier reports by Egbekun & Ehieze (1997) and Alobo et al (2009) have showed similar changes in soybeans, beniseed and cashew nut. The results showed that the energy value of the full-fat flour was higher than that of the defatted flour; this is because the fat content of a food material contribute more to its energy per unit weight than protein and carbohydrate contents.…”
Section: Proximate Compositionsupporting
confidence: 65%